2015
DOI: 10.3324/haematol.2014.116053
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional human CD56low CD16low natural killer cells are the prominent subset in bone marrow of both healthy pediatric donors and leukemic patients

Abstract: CD56high CD16+/-NK cells originate from CD34 + hematopoietic precursors through phenotypically distinct stages, whereas the CD56 low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 50 publications
9
75
2
Order By: Relevance
“…No significant difference in the CD56 dim CD16 dim NK subset was found between the chimeric and non-chimeric mice. However, the percentages of this population in bone marrow NK cells seemed to be higher than that recently reported for normal human bone marrow (28). Although there were no differences in any NK cell subsets in the peripheral blood of chimeric vs. non-chimeric mice, percentages of CD56 dim CD16 high and CD56 dim CD16 dim NK cells in human peripheral blood were significantly higher and lower, respectively, than those in the peripheral blood of both chimeric and non-chimeric mice.…”
Section: Resultscontrasting
confidence: 83%
“…No significant difference in the CD56 dim CD16 dim NK subset was found between the chimeric and non-chimeric mice. However, the percentages of this population in bone marrow NK cells seemed to be higher than that recently reported for normal human bone marrow (28). Although there were no differences in any NK cell subsets in the peripheral blood of chimeric vs. non-chimeric mice, percentages of CD56 dim CD16 high and CD56 dim CD16 dim NK cells in human peripheral blood were significantly higher and lower, respectively, than those in the peripheral blood of both chimeric and non-chimeric mice.…”
Section: Resultscontrasting
confidence: 83%
“…In contrast, Mamessier et al (25) observed that the amount of circulating CD56 bright NK cells in BC patients increased in relation to the grade of malignancy. This result was also observed in the blood and bone marrow of pediatric leukemic patients in comparison with age-matched healthy controls (26). A major modulation in the proportion of circulating CD56 bright NK cells was described in the blood of melanoma patients compared with healthy donors: they were increased almost 3.6-fold within peripheral NK cells (from 12.2 6 6.3% to 43.5 6 17.5%) (27,28).…”
Section: Cd56supporting
confidence: 59%
“…Moreover, HNSCC patients had decreased numbers of peripheral cytotoxic CD56 dim /CD16 + NK cells and a shift toward CD56 bright NK cells. A bias toward CD56 bright NK cell subpopulation and reduced CD16 expression was also described for patients with advanced cancers, such as melanoma, breast cancer, esophageal squamous cell carcinoma, and pediatric leukemia (7376). The reduction in CD16 + NK cell subsets is further correlated to decreased NK cell cytotoxicity and the immunosuppressive milieu of advanced cancers (73, 74, 77).…”
Section: Discussionmentioning
confidence: 81%